KARAKTERISTIK AKSEPTOR ALAT KONTRASEPSI DALAM RAHIM - Hasanah, Uswatun; Wahyuningsih, Heni Puji; Purnamaningrum, Yuliasti Eka (Poltekkes Kemenkes Yogyakarta, 2014)
The results of 2010's Population Census showed that population in Indonesia was 237.6 million. It was larger than the projected figure of 2010. Therefore, the government continues to suppress the rate of population growth, one ofmethod was Family Planning program(KB).The effectivemethod of birth controlwas intrauterine device (IUD), but its useinIndonesia wasstill quite low(7%),DIY (22.1%). Sleman (15.6%), inGodean I Public Health Centre (15.6%). The objective of this research was toknow the overview of the characteristics of IUD acceptors in Godean I Public Health Center 2010-2012. Methods: This study was descriptive quantitativeresearc h, with a cross-sectional approach, carried out inGodean I Public Health Center's region, Sleman, Yogyakarta in April 2013. The subjectswas 43 newIUDacceptors in 2010-2012 at Godean I Public HealthCenter. The datawas collected by using a formthat contains themedical record number, age, parity, education level and occupation. The datawas analyzed by using univariat analytic. Research Results: Active IUD acceptors in 2010-2012 amounted to 15% from5297 childbearing ages couple. Most of themwas in the age range after 30 years (69.8%),multiparous (81.4%), educated at the high school /vocational school (72.1%), and worked asprivate employees(37.2%).Conclusion:Most of theIUDacceptors inGodean I PublicHealthCenter in 2010-2012 waswomenin the ageof terminating pregnancy, have two children ormore, secondary' education and worked as private employees.